Perspectives on Microbiome Therapeutics in Infectious Diseases: A Comprehensive Approach Beyond Immunology and Microbiology - Hoonhee Seo; Sukyung Kim; Samuel Beck; Ho-Yeon Song (Cells)
Although global life expectancy has increased over the past 20 years due to advancements in managing infectious diseases, one-fifth of people still die from infections. In response to this ongoing threat, significant efforts are underway to develop vaccines and antimicrobial agents. However, pathogens evolve resistance mechanisms, complicating their control. The COVID-19 pandemic has underscored the limitations of focusing solely on the pathogen-killing strategies of immunology and microbiology to address complex, multisystemic infectious diseases. This highlights the urgent need for practical advancements, such as microbiome therapeutics, that address these limitations while complementing traditional approaches. Our review emphasizes key outcomes in the field, including evidence of probiotics reducing disease severity and insights into host-microbiome crosstalk that have informed novel therapeutic strategies. These findings underscore the potential of microbiome-based interventions to promote physiological function alongside existing strategies aimed at enhancing host immune responses and pathogen destruction. This narrative review explores microbiome therapeutics as next-generation treatments for infectious diseases, focusing on the application of probiotics and their role in host-microbiome interactions. While offering a novel perspective grounded in a cooperative defense system, this review also addresses the practical challenges and limitations in translating these advancements into clinical settings.